Yoga nidra [6th ed.] - Saraswati, Swami Satyananda (Munger Yoga Publications Trust, 1998)
Yoga Nidra is a simple yet profound technique adapted by Swami Satyananda Saraswati from the traditional tantric practice of nyasa.The Text explains the theory of Yoga Nidra in both yogic and scientific terms and includes class transcriptions of the practice.It also presents the various applications of this versatile technique,which has been used for deep relaxation,in stress management and therapy,to enhance the learning process in education,to harmonize the deeper unconscious and awaken inner potential,and as a meditative technique.A research section is also included.
Keywords: Yoga